Corporate Social Responsibility (CSR) dalam Isu-isu Globalisasi Ekonomi (Studi Tentang Sustainability CSR di Parawisata Pantai Duta Probolinggo) - mohammad syaiful suib; Nur Hasanatul Faizah (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2019)
Community empowerment through corporate social responsibility (CSR) funds has been intensively carried out by the company. As for research conducted: (1) obtaining an overview of CSR programs through empowerment carried out by PT. Jawa Power & PT. YTL East Java effectively; (2) knowing the strategies used so that the results of community empowerment can realize sustainable development. The method used with the qualitative Data used in qualitative includes primary data through observation and interviews and secondary data obtained from reference sources of books, journals, and mass media. Based on the results of CSR-based community empowerment research successfully implemented effectively if carefully planned and established good cooperation from the company and the community. To continue the sustainable development of the community who have been empowered to continue to apply the knowledge that has been gained during the training to be realized through the development of good infrastructure and tourism management systems.